2008
DOI: 10.1038/mt.2008.4
|View full text |Cite
|
Sign up to set email alerts
|

TAT-mediated Delivery of LAD Restores Pyruvate Dehydrogenase Complex Activity in the Mitochondria of Patients with LAD Deficiency

Abstract: Modern medicine offers no cure for mitochondrial disorders such as lipoamide dehydrogenase (LAD) deficiency. LAD is the E3 subunit shared by alpha-ketoacid dehydrogenase complexes in the mitochondrial matrix, and these complexes are crucial for the metabolism of carbohydrates and amino acids. We propose a novel concept for restoring the activity of an immense multicomponent enzymatic complex by replacing one mutated component, the LAD subunit. Our approach entails the fusing of LAD with the transactivator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…In 2008, the same protein was identified by Saada and her coworkers (15), in collaboration with our laboratory as an assembly factor.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…In 2008, the same protein was identified by Saada and her coworkers (15), in collaboration with our laboratory as an assembly factor.…”
Section: Introductionmentioning
confidence: 77%
“…Inside the mitochondria, TAT-LAD is processed normally and restores LAD activity. Most importantly, we showed that TAT-LAD is able to almost completely restore the activity of the mitochondrial multienzyme pyruvate dehydrogenase complex (PDHC) within the treated patients' cells (15). Moreover, we demonstrated the delivery of TAT-LAD into E3-deficient mice tissues and that a single administration of TAT-LAD results in a significant increase in the enzymatic activity of PDHC within the liver, heart and mainly the brain of TAT-LAD-treated E3-deficient mice (27).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations